Cats - Posell, Elsa Z. (Chicago : Childrens Press, 1983)
A guide to caring for cats as pets, which includes descriptions of other members of the cat family.
Includes index.
3.3
K-3
K-4.
Keywords: Cats -- Juvenile literature; Felidae -- Juvenile literature; Cats; Felidae; Cats